2016
DOI: 10.1038/nrneurol.2016.88
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor: a neurovascular target in neurological diseases

Abstract: Brain function critically relies on blood vessels to supply oxygen and nutrients, to establish a barrier for neurotoxic substances, and to clear waste products. The archetypal vascular endothelial growth factor, VEGF, arose in evolution as a signal affecting neural cells, but was later co-opted by blood vessels to regulate vascular function. Consequently, VEGF represents an attractive target to modulate brain function at the neurovascular interface. On the one hand, VEGF is neuroprotective, through direct effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
283
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(292 citation statements)
references
References 199 publications
6
283
0
3
Order By: Relevance
“…Interference with VEGF signaling may contribute to the inhibitory effects of Aβ42 on synaptic transmission [77][78][79]. Indeed, VEGF administration has been investigated as a neuroprotective, proangiogenic therapy in AD [80][81][82]. The present study adds to our understanding of VEGF-VEGFR signaling in AD.…”
Section: Discussionmentioning
confidence: 76%
“…Interference with VEGF signaling may contribute to the inhibitory effects of Aβ42 on synaptic transmission [77][78][79]. Indeed, VEGF administration has been investigated as a neuroprotective, proangiogenic therapy in AD [80][81][82]. The present study adds to our understanding of VEGF-VEGFR signaling in AD.…”
Section: Discussionmentioning
confidence: 76%
“…The activation of the VEGFR2 and Wnt-β-catenin pathways in BECs have been shown to induce angiogenesis and mature vessel morphology in the developing CNS (9)(10)(11)(12). Subsequently, TGF-β/TGF-βR and Ang-1/Tie-2 signaling promote further BBB maturation (6).…”
mentioning
confidence: 99%
“…40) The beneficial effects of anti-VEGF neutralizing antibody on t-PA-induced BBB disruption and hemorrhage were also reported. 41) As summarized by Lange et al, 42) VEGF was reported to be a therapeutic target for BBB disruption and a therapeutic target for several other neurological disorders.…”
Section: )mentioning
confidence: 99%